The Influence of ZnCl2 Activation on Macronutrient NPK Adsorption Simultaneously Using Coconut Shell Biochar for Soil Fertility Improvement - Candra Purnawan; Christina Candra Dewi; Syafrudin syafrudin; Bimastyaji Surya Ramadan; Mochamad Arief Budihardjo; Agus Jatnika Effendi; Syarif Hidayat (Universitas Jenderal Soedirman, 2021)
The influence of ZnCl2 activation on macronutrient Nitrogen, Phosphor, Potassium (NPK) adsorption simultaneously using Coconut Shell Biochar for soil fertility improvement has been conducted. Biochar formation is carried out at temperature up to 500 oC using variation in the concentration of ZnCl2 0,5; 1,0; 1,5; 2,0; dan 2,5 M. The biochar formed was characterized using Fourier Transform InfraRed (FTIR) spectroscopy and Surface Area Analyzer (SAA). Whereas NPK analysis has used the Indonesian standard method (SNI 7763: 2018). Based on this research, it was concluded that the greater the concentration of ZnCl2 activator, indicated that the higher intensity of the spectra of –OH and –NH2 at wave number 3400 cm-1 and 1600 cm-1. It showed that biochar activation was higher and a more active functional group was opened. Increasing the concentration of ZnCl2 activator has increased Biochar adsorption of NPK macronutrients. The optimum condition for activation of coconut shell Biochar was activation with ZnCl2 2.5 M. The addition of activated Biochar was increased soil adsorption on NPK macronutrients. Biochar addition had increased Nitrogen (N) adsorption up to 23.53%, Phosphor (P) up to 200%, and Potassium (K) up to 41.24%.